How do esters and dimethyl sulphide concentrations affect fruity aroma perception of red wine? Demonstration by dynamic sensory profile evaluation. (1st March 2016) - Lytra, Georgia; Tempere, Sophie; Marchand, Stéphanie; de Revel, Gilles; Barbe, Jean-Christophe
Highlights: Dynamic sensory profiles evince fruity aroma evolution during sensory analysis. Modification of a wine's fruity notes during a 30-min sensory analysis. Decrease in ester and dimethyl sulphide concentrations in the first few minutes. Aromatic reconstitutions prove the olfactory impact of esters and dimethyl sulphide. Dimethyl sulphide and esters participate in modulating fruity aromas in red wine. Abstract: Our study focused on variations in wine aroma perception and molecular composition during tasting over a period of 30 min. In parallel, dynamic analytical and sensory methods were applied to study changes in the wines' molecular and aromatic evolution. Dynamic sensory profile evaluations clearly confirmed the evolution of the wine's fruity notes during sensory analysis, highlighting significant differences for red-berry and fresh fruit as well as black berry and jammy fruit, after 5 and 15 min, respectively. Dynamic analytical methods revealed a decrease in ester and dimethyl sulphide (DMS) concentrations in the first few minutes. Sensory profiles of aromatic reconstitutions demonstrated that the aromatic modulation of fruity notes observed during wine tasting was explained by changes in ester and DMS concentrations. These results revealed that variations in concentrations of DMS and esters during wine tasting had a qualitative impact, by modulating fruity aromas in red wine.